2022
DOI: 10.1039/d2ta00765g
|View full text |Cite
|
Sign up to set email alerts
|

In operando identification of the V4+-site-dependent nitrogen reduction reaction of VSx

Abstract: The unique d orbital electron configuration of transition-metal elements endows the metal centers of transition metal-based materials (TMs) with multiple valence features. However, the metal valence state dependent activity of...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 40 publications
2
11
0
Order By: Relevance
“… The decrease in intensity and the widening of the peak show that certain V–S bonds are cleaved after activation. The intensity maxima of the WT-EXAFS spectra for both the initial and activated V-NiS samples were observed at different R space values of 2 and 1 Å, respectively, indicating the presence of two different coordination structures for V–S bonds (Figure i,j) . This confirms the previous DFT calculations, which showed that the incorporation of V atoms induces charge redistribution of the surrounding S atoms and leads to asymmetry.…”
supporting
confidence: 87%
“… The decrease in intensity and the widening of the peak show that certain V–S bonds are cleaved after activation. The intensity maxima of the WT-EXAFS spectra for both the initial and activated V-NiS samples were observed at different R space values of 2 and 1 Å, respectively, indicating the presence of two different coordination structures for V–S bonds (Figure i,j) . This confirms the previous DFT calculations, which showed that the incorporation of V atoms induces charge redistribution of the surrounding S atoms and leads to asymmetry.…”
supporting
confidence: 87%
“…As known, a good catalyst should offer the efficient adsorption of reactant wherein the nitrogen adsorption should be energetically preferred and the hydrogen adsorption should be relative weaker in order to suppress the undesirable competition from the side hydrogen evolution reaction (HER) in aqueous solution. [37,41] Therefore, the first screening parameters are adsorption free energy of nitrogen molecule G ads (*N 2 ) and the difference of the adsorption free energies between nitrogen moleucle and hydrogen atom, that is, ΔΔG ads = G ads (*N 2 )À G ads (*H). In addition, since the potential-determining step (PDS) is usually located at the first protonation (*N 2 !…”
Section: Resultsmentioning
confidence: 99%
“…The identification of N 2 H y as the reaction intermediates by SERIAS indicated that the ENRR on Au surfaces follows the associative mechanism [99] . Other operando spectroscopic techniques including Raman spectroscopy and XRD have been utilized to identify active sites and the reaction mechanisms for the ENRR on different catalysts [101–107] . Combined with other ex situ and in situ characterization results, the V 4+ site was demonstrated to be responsible for the high ENRR performance on VS 2− x catalysts [106] .…”
Section: Discussionmentioning
confidence: 99%
“…Other operando spectroscopic techniques including Raman spectroscopy and XRD have been utilized to identify active sites and the reaction mechanisms for the ENRR on different catalysts [101–107] . Combined with other ex situ and in situ characterization results, the V 4+ site was demonstrated to be responsible for the high ENRR performance on VS 2− x catalysts [106] . The direct observation of electric double layer region on TMN catalysts using different operando spectroscopic techniques can help identify the possible reaction intermediates, solvent and cation effects, reaction mechanisms, and thus guide the optimization of electrocatalysts and electrolytes.…”
Section: Discussionmentioning
confidence: 99%